STUDI PEMBERIAN INFORMASI TENTANG TEKNIK PENGGUNAAN METERED DOSE INHALER OLEH APOTEKER DAN TENAGA TEKNIS KEFARMASIAN DI APOTEK KECAMATAN MERTOYUDAN, KABUPATEN MAGELANG - Heni Lutfiyati; Tiara Mega Kusuma; Septi Wardani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Asthma is a serious health problem and can attack all age groups. Inhalation of drugs is the most important route in the management of asthma. The purpose of this study was to find out the description of the provision of information about the technique of using Metered Dose Inhalers by pharmacists and pharmacy technician at the Mertoyudan District pharmacy, Magelang District. This research is a descriptive study using the investigation research approach that is gathering information related to the provision of information on the use of Metered Dose Inhaler techniques by pharmacists and pharmacy technicians by means of investigation. The data obtained is then analyzed and made conclusions. The variables in this study are providing information about the use of Metered Dose Inhalers by pharmacists and pharmacy technicians. Data collection was carried out in February 2018. The population in this study were all pharmacists and pharmacy technicians in the Mertoyudan District, Magelang District. The sample in this study is Pharmacists and Pharmacy technicians who practice in the pharmacy of the Mertoyudan District Region, Magelang District. Observations made by researchers in Mertoyudan District with a total of 15 pharmacies, obtained 40% of pharmacies available inhaler drugs and 60% of pharmacies are not available because rarely patients buy and the price of drugs is expensive. The results showed that from 9 stages of using Metered Dose Inhalers, all respondents demonstrated the opening and closing stage of the inhaler and press the canister and only 6.67% gave information slowly exhaling until there was no remaining air to be exhaled. The conclusion of the pharmacist who provided complete information about the technique of using inhalers was 6.67%.